International consensus diagnostic criteria for autoimmune pancreatitis: guidelines of the International Association of Pancreatology - Shimosegawa, Tooru; Chari, Suresh T.; Frulloni, Luca; Kamisawa, Terumi; Kawa, Shigeyuki; Mino-Kenudson, Mari; Kim, Myung-Hwan; Klöppel, Günter; Lerch, Markus M.; Löhr, Matthias; Notohara, Kenji; Okazaki, Kazuichi; et al. (Pancreas, 2011)
Objectives: To achieve the goal of developing international consensus diagnostic criteria (ICDC) for autoimmune pancreatitis (AIP). - Methods: An international panel of experts met during the 14th Congress of the International Association of Pancreatology held in Fukuoka, Japan, from July 11 through 13, 2010. The proposed criteria represent a consensus opinion of the working group. Results: Autoimmune pancreatitis was classified into types 1 and 2. The ICDC used 5 cardinal features of AIP, namely, imaging of pancreatic parenchyma and duct, serology, other organ involvement, pancreatic histology, and an optional criterion of response to steroid therapy. Each feature was categorized as level 1 and 2 findings depending on the diagnostic reliability. The diagnosis of type 1 and type 2 AIP can be definitive or probable, and in some cases, the distinction between the subtypes may not be possible (AIP-not otherwise specified). Conclusions: The ICDC for AIP were developed based on the agreement of an international panel of experts in the hope that they will promote worldwide recognition of AIP. The categorization of AIP into types 1 and 2 should be helpful for further clarification of the clinical features, pathogenesis, and natural history of these diseases.